Influence of Leadership, Human Resource Development and Employee Engagement Affecting The Employee Intentions to Stay in Factories of Electronic Industry Group - Namwongsa, Somjai; Nertepradit, Napawan; Yavirach, Natepanna (Journal of Humanities and Social Sciences Thonburi University, 2020)
This research was a mixed methods research using quantitative and qualitative research methods. The objectives were (1) to study the causal influence of leadership, human resource development, employee engagement, and employee's intention to stay in the organization and (2) to present the pattern that support the employee's intention to stay in the organization. The sample group included 500 employees having lower positions than managers from the factories of electronic industry group in the Northern Region Industrial Estate of Thailand. The questionnaire was a research tool for data collection and analysis of structural equation models using statistical software program. For qualitative research tool was structure in-depth interview for 15 employees. The results of the study indicated that the factors of transactional leadership had a direct effect on human resource development, transformational leadership had a direct effect on employee engagement, human resource development had a direct effect on employee engagement, and employee engagement had a direct effect on employee's intention to stay in the organization with statistical significance 0.01, respectively. Transformational leadership had no direct effect on human resource development and transactional leadership had no direct effect on employee engagement with statistical significance 0.01 respectively. The qualitative research results are consistent and support with quantitative research results in every aspect.